Allometry and morphological trait relationship in the sexually dimorphic Chinese dobsonfly, Acanthacorydalis asiatica (Wood-Mason, 1884) (Megaloptera, Corydalidae) - Chengquan Cao; Pei Yu; Fumio Hayashi (ZooKeys, 2019)
Male insects with large weapons such as horns and elongate mandibles would be expected to invest more on such structures than other parts of the body for advantages in male to male competition for mating. In male genitalia, however, intermediate size provides a better fit for more females than small or large sizes, and such a male would leave more offspring regardless of their body size. These predictions were tested using a static allometry analysis between body size and other trait sizes. Acanthacorydalis asiatica is a large dobsonfly (Megalotera) and males have conspicuously large mandibles used as weapons. We examined the hypothesis that the male mandibles of this sexually dimorphic species are sexually selected to enlarge, whereas the male genitalia are stable to be intermediate regardless of a great variation in body size. The results, as predicted, showed positive allometry between male body size and mandible length but negative allometry between male body size and ectoproct length (a male grasping structure). Sperm are transferred through a small spermatophore attached externally to the female genital opening, so it may be evolutionarily unnecessary to develop an enlarged male genital size. In contrast, there may be a trade-off between male mandible size and wing length, because of negative allometry between body size and wing length in males but isometry between them in females.